A Facilitating Effective Teaching through Learning Based on Learning Styles and Ways of Thinking - Ginting, Siti Aisyah (IAIN Samarinda, 2017)
The study deals with learning styles and ways of thinking in facilitating effective teaching. The objective of this study was to investigate the relationship between studentsâ€™ learning style and ways of thinking toward effective teaching. This study was conducted by using correlational design. The population of the study were 360 university students of English education academic yearÂ 2015/2016 in State University of Medan. The samples were 82 university students selected by using random sampling. The data were collected by using questionnaires and tests. The analysis used the techniques of regression and correlation. The finding of this study revealed that F count is higher that F table ( F count =13.67Â > F table =3.32 ; the correlation coefficient (ry 12) = 0.57) meaning that there is significant correlation between learning styles and ways of thinking. It indicates that learning styles and ways of thinking contribute to effective teaching.